Environmental Biotechnology - Banerjee, Rintu (Oxford University Press, Incorporated, 2008)
Annotation Environmental Biotechnologydiscusses the development, use, and regulation of biological systems for remediation of contaminated environments and for environment friendly processes. The book begins with a definition of relevant terms, a discussion of different types of pollution and wastes and goes on to provide exhaustive coverage of the treatment of liquid and solid wastes, economic and social aspects of waste treatment, and the analytical methods for environmental monitoring. The book also includes a separate chapter on the stoichiometry and reaction kinetics essentail for the design of bioreactors. This book concludes with a case study of the design and economic evaluation of an integrated biogas plant for a dairy farm. Written in a lucid style, the book should be useful to students of both engineering and bioscience.
Keywords: Bioremediation.; elektronické knihy; electronic books